Sexual Dysfunction in Post-Stroke Patients - Purba, Sri Dearmaita; Sijabat, Flora; Amila, Amila (International Journal of Nursing and Health Services (IJNHS), 2024)
Introduction: Stroke is a leading cause of death and disability worldwide. Currently, there is a pattern of shifting stroke epidemiology towards the young and productive age range of 18-45 years due to lifestyle. Post-stroke physical and cognitive impairments have been well studied, little is known about sexual function and satisfaction in these patients, despite it being an important aspect of quality of life. The problem of sexual dysfunction in young post-stroke patients is rarely detected and given less attention as the patient's recovery focuses on daily functional ability. Objective: To identify young adult post-stroke patients with disability with sexual concerns, functional status and quality of life. Method: The study used quantitative methods (descriptive research) with a cross sectional design using purposive sampling totaling 29 people in young adult post-stroke patients (18-45 years old) at Dr. Pirngadi Medan Hospital. Data collection instruments used the Changes in Sexual Functioning Questionnaire (CSFQ-14) to assess sexual changes, Stroke-Specific Quality of Life (SS-QoL-12) to assess quality of life and Barthel Index (IB) to assess functional ability. The study data were analyzed using the SPSS program. Results: There were 29 subjects with a mean age of 39.07±6.39 years, mainly male (58.6%) and suffering from ischemic stroke (89.7%). The majority of subjects had sexual dysfunction (82.3%), mild dependence (65.5%) and high quality of life (58.6%). Recommendation: Nurses need to screen and evaluate post-stroke sexual dysfunction, so that neuro-rehabilitation can be done to improve the patient's quality of life. Keywords: Dysfunction, Stroke, sexual, young age